Independent Control of Two-PMSM Fed by Two SVPWM Inverters with Fault Tolerant Operation - Chasib, Ahmed J.; Abdulabbas, Ali K.; Obed, Adel A. (Basrah Journal for Engineering Sciences, 2016)
This paper presents an implementation of an independent control of two-mechanically coupled Permanent Magnet Synchronous Motor (PMSM) fed by two Space Vector Pulse Width Modulation (SVPWM) inverters in a separate mode and in the event of failure one leg of one inverter, fault tolerant mode. In a fault tolerant mode, the two motors can operate in an independent control strategy from one inverter with five legs to maintain a constant output coupled torque. The Field Oriented Control (FOC) strategy is used to control the stator current of the two motors through two separate paths. Such application is used in the field of a coupled torque produced by multi-motors such as in subway applications. The whole system is simulated in Matlab /Simulink and the simulated results show a stable and robustness system which can maintain a constant developed torque with a velocity reaches to the rated under fault tolerant operation.